N-Substituted tetrahydro-2,4-dioxoquinazolin-1-yl acetic acids as aldose reductase inhibitors - Rakowitz, D.; Gmeiner, A.; Matuszczak, B. (Pharmazie, 2007)
Novel N-substituted tetrahydro-2,4-dioxoquinazolin-1-yl acetic acids characterized by formal replacement of the substituted benzyl moiety by cyclohexylmethyl and n-heptyl residues, respectively, were synthesized and evaluated as aldose reductase inhibitors.